A strategy to introduce gradient equiaxed grains into Zr sheet by combining laser surface treatment, rolling and annealing. (15th April 2021) - Chai, Linjiang; Zhu, Yufan; Hu, Xing; Murty, Korukonda L.; Guo, Ning; Chen, Liang-Yu; Ma, Yanlong; Zhang, Lai-Chang
Abstract: A novel strategy combining laser surface treatment, rolling and annealing (LST-RA) to produce gradient equiaxed grains is proposed and verified after applying to pure Zr sheet. Dense high angle boundaries (HABs) are first produced by the laser-induced rapid β→α transformation in the surface layer of pure Zr while a considerable amount of stored energy is then introduced by 50% rolling. During subsequent annealing, the preexisting denser HABs facilitate generating more recrystallization nuclei in the surface layer than in the matrix through the strain induced boundary migration mechanism. This eventually results in a gradient equiaxed grain structure from surface to interior of the pure Zr sheet. Furthermore, the fine-grained surface layer is found to have a weakened texture compared to the coarse-grained matrix. Graphical abstract: Image, graphical abstract